Therapeutic Potential of Dhataki (Woodfordia Fruticosa) In the Management of Pradar Roga: An Ayurvedic and Pharmacological Review - Bharati, Sarswati; Tiwari, Sampurnanand (Journal of Neonatal Surgery, 2025)
Pradar Roga, a prevalent gynecological condition in women, is broadly correlated with leucorrhea in modern medicine and is characterized by excessive, abnormal vaginal discharge. In Ayurveda, its pathogenesis is primarily attributed to the vitiation of Kapha and Pitta doshas with the involvement of Apana Vata and Artavavaha srotas. Among the various herbal remedies described, Dhataki (Woodfordia fruticosa Kurz) holds significant therapeutic relevance due to its stambhana (astringent) and rakta stambhaka (hemostatic) properties. Classical Ayurvedic texts, along with contemporary pharmacological evidence, suggest its efficacy in controlling excessive discharge, reducing inflammation, and promoting mucosal healing. Phytochemical analysis reveals the presence of tannins, flavonoids, phenolic compounds, and anthocyanins, contributing to its antimicrobial, anti-inflammatory, antioxidant, wound-healing, and immunomodulatory actions. Clinical studies further support its role in alleviating symptoms, improving local tissue integrity, and enhancing patient quality of life. This review critically synthesizes classical references, pharmacological data, and clinical research on Dhataki in the management of Pradar Roga, identifies research gaps, and proposes directions for future evidence-based application in gynecological practice.